An exploration of intimate partner violence, stalking and image-based sexual abuse in intimate relationships - Phipps, Kate (2022)
This thesis provides an original contribution to the literature by exploring the intersection between intimate partner violence (IPV), stalking and image-based sexual abuse (IBSA). The overall aim is to improve the current understanding and knowledge of the relationship between these behaviours and likely characteristics of such perpetrators as the overlap between IPV, stalking and IBSA is yet to be adequately understood. Considering the risk of individuals engaging in multiple types of abusive or controlling behaviours in intimate relationships, it is important to understand the characteristics and factors that underpin the perpetration of these offences. This insight could contribute to how practitioners understand and manage such perpetrators through assessment and intervention. A range of methods were used, including a systematic review, two empirical research studies and a psychometric critique. Following an introduction in Chapter One which provides a general overview of the literature and aims of the thesis, Chapter Two contains a systematic review of the literature on the prevalence and characteristics of co-occurring IPV and stalking perpetration. The results of this review indicate that there are variables which differentiate perpetrators who engage in co-occurring IPV and stalking perpetration from IPV-only or stalking-only perpetrators. However, these findings are impacted upon by definitional and methodological problems which highlights the need for further high-quality research.